The Influence of Android-Based Mobile Learning on Students' Learning Independence on the Subject of Derivative Algebraic Functions - Siti Kurniasih (ITEJ (Information Technology Engineering Journals), 2019)
The purpose of this research are: 1) to find out how much student’s self regulated learning in using android-based mobile learning, 2) to determine students’ responses about the using of android-based mobile learning in mathematics learning, and 3) to determine whether or not there is an influence of android-based mobile learning on students’ self regulated learning. Metodology in this research is using the experimental method with data collection techniques in the form of questionnaires for the two variables. The population in this research are all students of the clas XI Science in SMAN 1 Astanajapura, while the research sample is XI Science 4 class which was selected using cluster random sampling technic. Based on the results of the research, it can be concluded that the results of the student response questionnaire in using android-based mobile learning show strong criteria with an average percentage of 70.7% and the results of the students’ self regulated learning questionnaire show strong criteria with an average percentage of 73.7%. After hypothesis testing with , it can be seen that the value of is . Because then is rejected and is accepted, meaning that there is a significant influence between the using android-based mobile learning on students’ self regulated learning. The magnitude of the coefficient of determination obtained is 0.423 or 42.3% which means that the using of android-based mobile learning has an effect of 42.3% on students’ self regulated learning and the rest in influenced by other factors. Keywords: Instructional Media, Android-Based Mobile Learning, Self Regulated Learning